Fra kollektiv til konnektiv handling? Nye former for samfunnsengasjement og kollektiv handling i Norge - Enjolras, Bernard (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"Volunteering and political activism are two key forms of civic engagement. There is a broad consensus that civic engagement, which often involves participation in various forms of collective action, is a cornerstone of a well-functioning democracy. Civic engagement and participation in collective action have traditionally been linked to social movements and voluntary organizations. Collective action is, however, changing as a result of societal- level processes of change, such as digitalization, the emergence of social media, individualization and globalization. This book investigates how these social changes have affected the ways individuals participate in different forms of collective action. What consequences does digitalization have for civic engagement in Norway? Is the distinction between volunteering and political activism about being wiped out? Are new organizational forms arising as a result of digitalization and individualization? Has globalization led to new forms of transnational networks? And more generally, are the traditional forms of collective action, rooted in civil society organizations, replaced by a new form of ""connective action""? Based on a variety of data sources, including survey data, case studies and in-depth interviews, the authors paint a broad picture of how different forms of collective action and civic engagement in Norway are influenced by processes of social change. The analyzes in this book are based on a five-year research project within the Center for Research on Civil Society and Voluntary Sector, funded by the Ministry of Culture. The book presents the project's main findings in an edited volume with contributions from an interdisciplinary team of authors."